Biochemical Reasons for the Presence of the Limiting Character of Thrheonine in Some Mammals and the Absence of the Limiting Character of Threonine in Humans (Global Journal of Medical Research, 2023)
Abstract not found
Keywords: threonine; transamination; pigs; a human